2021
DOI: 10.1186/s13033-021-00478-8
|View full text |Cite
|
Sign up to set email alerts
|

Lay social workers implementing a task-sharing approach to managing depression in Vietnam

Abstract: Background While depression is a leading contributor to burden of disease in Vietnam, there is a critical gap in depression care due to the shortage of mental health specialists and extremely limited mental health services in general health care settings. We have previously reported the effectiveness of a supported self-management (SSM) task-sharing intervention for depression, delivered by social collaborators (lay social workers). The purpose of this study was to identify factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Supported self-management (SSM) is an evidence-based approach to the management of chronic disease which empowers the patient to participate in their own care by building appropriate skills with the support of a physician, lay provider, or other carer [31]. The in-person SSM for depression intervention that was previously tested [25] included a cognitive-behavioural therapy (CBT)-informed bibliotherapy intervention provided via the ASW [32] with supportive coaching provided face-to-face by non-specialist providers [33]. For the digital intervention used in this study, ASW was adapted to be delivered via the VMood smartphone app, with supportive coaching as needed provided through an online chat function by social workers.…”
Section: Interventionsmentioning
confidence: 99%
“…Supported self-management (SSM) is an evidence-based approach to the management of chronic disease which empowers the patient to participate in their own care by building appropriate skills with the support of a physician, lay provider, or other carer [31]. The in-person SSM for depression intervention that was previously tested [25] included a cognitive-behavioural therapy (CBT)-informed bibliotherapy intervention provided via the ASW [32] with supportive coaching provided face-to-face by non-specialist providers [33]. For the digital intervention used in this study, ASW was adapted to be delivered via the VMood smartphone app, with supportive coaching as needed provided through an online chat function by social workers.…”
Section: Interventionsmentioning
confidence: 99%
“…According to Bassuk, Glass & Berkman (1991), social engagement is a form of maintaining social relations in the form of individual social interactions through facilitated social activities (26). The results of the research showed that what is done in a company, that social engagement as a strength possessed by individuals who act as an internal stakeholders in the company can create social capital, provide social resources, loyalty, and trust that will have implications for future development (27), using a social engagement approach to overcome various mental health problems in the community (28), the negative stigma for PLWHA that develops in the community can be controlled through a social engagement approach by increasing HIV care and prevention (29), early depression associated with peptic ulcer disease in the elderly can be reduced by increasing social engagement in social activities (30), social engagement contributes to cognitive changes in disease-prone groups in the elderly who suffer from Alzheimer's (31), the social engagement approach can describe the problem of limited energy access in Spain by providing a basic understanding, socialization aimed at leading to institutional responses and policy making, as well as a deeper understanding related to the confrontation of unequal access issues. to energy resources (32), social engagement approaches can be found through participation in income-generating activities, community activities, and care work (33).…”
Section: Introductionmentioning
confidence: 99%